2003
DOI: 10.1007/s00264-003-0467-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the growth plate in late-onset tibia vara

Abstract: We used Magnetic resonance imaging (MRI) in five patients (six knees), mean age 13.2 (12-15) years, with late-onset tibia vara (Blount's disease), to study the growth plate and its abnormalities. The MRI study was classified for severity of disease and compared with a radiographic classification. In severely involved knees, MRI indicated severe growth-plate changes on both sides of the knee joint. Widening in the entire proximal tibial growth plate, involvement of the distal femoral growth plate, as well as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…When applying MRI, no radiation exposure is required. However, until now, MRI measurements have only been introduced into the diagnosis of leg deformities for femoral anteversion in pediatric patients with femoral [11] and growth-plate changes in tibia vara prior to oblique osteotomy or tibial hemiepiphysiodesis [12]. These applications are based on axial MRI images at the center of the main magnetic field and, hence, the gradient fields used for image reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When applying MRI, no radiation exposure is required. However, until now, MRI measurements have only been introduced into the diagnosis of leg deformities for femoral anteversion in pediatric patients with femoral [11] and growth-plate changes in tibia vara prior to oblique osteotomy or tibial hemiepiphysiodesis [12]. These applications are based on axial MRI images at the center of the main magnetic field and, hence, the gradient fields used for image reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has not yet been established for preoperative planning of corrective surgery, even though first experiences in the comparison of radiography, CT, and MRI on cadaveric femurs have been published [10]. Currently, MRI is part of the diagnostic procedure only in pediatric patients with femoral anteversion prior to rotation osteotomies [11] and growth-plate changes in tibia vara prior to oblique osteotomy or tibial hemiepiphysiodesis [12]. The technical limitations are that the field of view (FoV) of typical clinical scanners does not allow imaging of objects larger than 50 cm without table movement and that conventional high-field (> 1 Tesla) MRI systems cannot simulate the effect of full weight bearing on the limb axis because of the supine imaging position.…”
Section: Introductionmentioning
confidence: 98%
“…Ferriter and Shapiro [9] found a clear difference, such that there was a recurrence rate of 76 % in limbs operated initially at age older than 4.5 years versus 31 % recurrence rate before 4.5 years. Many reports concluded that (a) operative treatment should be performed before the age of four years on patients with progressive clinical and radiographic evidence of Blount disease, (b) surgical correction should be performed when radiographic stage shows the patient had Blount disease corresponding to Langenskiöld stage I or II, (c) a single corrective osteotomy performed early on the affected limb could result in permanent correction which could significantly decrease the incidence of a symptomatic and painful knee at maturity, and (d) failure to correct the tibia vara early will result in permanent physeal damage and development of degenerative intra-articular knee pathology, including meniscal tears and degenerative articular cartilage changes [12,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There is invagination of cartilage into the tibial and femoral metaphyses. Bone may bridge the physis [ 27 ] (Fig. 14.26 ).…”
Section: Imagingmentioning
confidence: 98%